2017
DOI: 10.4236/jpee.2017.512005
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the Cycle Performance of LiNi<sub>0.5</sub>Mn<sub>1.5</sub>O<sub>4 </sub> Cathode Active Materials by In-Situ Coating with Poly(3,4-Ethylenedioxythiophene)

Abstract: LiNi 0.5 Mn 1.5 O 4 (LNMO)/poly(3,4-ethylenedioxythiophene) (PEDOT) composite cathode materials were prepared through in-situ polymerization of thiophene monomer (EDOT), with ammonium persulphate (APS) as oxidizing agent, p-toluenesulfonic acid (PTSA) as dopant. The morphology, amount of PEDOT coating, electrochemical properties of LNMO/PEDOT were characterized by scanning electron microscopy (SEM), thermogravimetric analysis (TGA) and galvanostatic charge and discharge tests. The results show that the composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…The good cycling stability of LMNO-PE could be related to the ability of PEDOT:PSS to be a "barrier" against undesired side reactions of LMNO with the electrolyte. On the other hand, this effect has already been observed for cathodes produced with PVdF binder and PEDOT:PSS-coated LMNO particles [19][20][21][22][23]. Hence, this work demonstrates that it is possible to produce LMNO cathodes with aqueous binders maintaining the same performance of PVdF, in the case of pullulan, and improving them by the direct use of an electronically conductive binder such as PEDOT:PSS, without the need of LMNO particle coating.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The good cycling stability of LMNO-PE could be related to the ability of PEDOT:PSS to be a "barrier" against undesired side reactions of LMNO with the electrolyte. On the other hand, this effect has already been observed for cathodes produced with PVdF binder and PEDOT:PSS-coated LMNO particles [19][20][21][22][23]. Hence, this work demonstrates that it is possible to produce LMNO cathodes with aqueous binders maintaining the same performance of PVdF, in the case of pullulan, and improving them by the direct use of an electronically conductive binder such as PEDOT:PSS, without the need of LMNO particle coating.…”
Section: Discussionsupporting
confidence: 57%
“…The resulting material has been exploited to prepare electrodes with a PVdF-binder. PEDOT-coated LMNO particles featured a better capacity retention with respect to the pristine material, with improved gravimetric capacity [19]. Laisuo et al showed that a protective thin film of PEDOT on LMNO obtained by chemical vapor deposition (CVD) increases the rate capacity and extends the high temperature (50 • C) cycle life of LiMn 2 O 4 by over 60% [20].…”
Section: Introductionmentioning
confidence: 99%
“…01-089-3604. The occurrence of the impurity phase is also reported in the literature. The Rietveld refinement analysis quantifies the impurity phase to be 4 wt % in both LNMO and C-LNMO. Therefore, the more suitable notation for the LNMO phase is LiNi 0.5– x Mn 1.5+ x O 4 .…”
Section: Resultsmentioning
confidence: 62%
“…Therefore, the carbon coating offers a unique solution that combines all of the desired advantages. Several carbonaceous materials are reported in the literature that include camphoric carbon, graphene oxide, reduced graphene oxide, carbon nanotubes, heteroatom-doped carbons, sucrose-derived hard carbons, and conductive polymers such as polythiophene, polyimide, polyacrylonitrile, PANI, PEDOT, and so forth. The surface protection and enhancement in electronic conductivity are successfully achieved by applying such coatings. However, the surface heterogeneity, doped heteroatoms, and functional groups catalyze the electrolyte decomposition .…”
Section: Introductionmentioning
confidence: 99%